Penyuluhan Kesehatan Senam Hipertensi Terhadap Penurunan Tekanan Darah Pada Masyarakat Wilayah Rw 07 Rt 08 Kelurahan Gembor Wilayah Puskesmas Gembor - Siti Robeatul Adawiyah; Eni Hernawati; Lutfiah Galuh Ayu; Siti Homalia; Ayu Diah Faradina; Arum Arofiyah Wiharti; Deva Restu Sari; Erna Susanti; Ainul Latifah; Sulyanti Suhartini; Ayu Aulia; Regita Citra; Rahma Nurazizah; Hilda Nuramaliyah; Ratih Pisesa Pebrianti; Fauzy Rakha (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hypertension or high blood pressure is a chronic condition characterized by increased blood pressure on the walls of the arteries. This situation causes the heart to work harder to circulate blood throughout the body through blood vessels, even causing degenerative diseases and even death. The purpose of hypertension exercise is to increase the knowledge of residents in Gembor village RW 007 RT 008 Persada Total Housing related to hypertension exercise to reduce blood pressure. The method used is by socializing and providing counseling about the steps in hypertension exercise. Health counseling was held on Saturday 1 July 2023. The population in this counseling were residents of RW 007 Persada Total Housing. After carrying out health education about hypertension, it was found that 55.2% of the residents understood, understood and were able to give an example of how to exercise hypertension to reduce blood pressure.